Unofficial cultural ambassadors: exploring the experiences and perceptions of Malaysian student scholars in America - Wan Mohd Nor, Sofiya; Wan Mohd Nor, Murni (Penerbit Universiti Sains Malaysia, 2024)
International educational exchange programmes promote a person’s intellectual development and cultural understanding, which could also foster mutual cooperation and stronger diplomatic ties between countries. Through these programmes, students can socially interact and learn about others from diverse backgrounds. However, the rise of Islamophobia after the September 11 attacks has inculcated the fear of “the Other” and limited the number of Muslim students allowed to study in America, as Muslim culture and religious values are popularly perceived as incompatible with American values and thus viewed as a threat. This study contributes to the literature of diplomacy by highlighting the experiences of sixteen Malaysian scholars sponsored by the Malaysian government and the challenges they experienced during their educational exchange in America. The aim of this qualitative study is to understand the experiences of Malaysian student scholars by identifying: (1) how they initially perceived America; (2) their motivations for wanting to study in America; (3) the challenges they faced; and (4) how their experiences transformed them. The study found that many students faced initial struggles with racism, cultural challenges, and difficulty in achieving cultural assimilation. However, they were able to overcome misperceptions and negative stereotypes. The findings highlight the positive impact of their academic and cultural exchange, its success in reducing divisiveness, and the influence of soft power in strengthening relations between America and Malaysia.